Preparation of an economic home-made Ag/AgCl electrode from silver recovered from laboratory wastes - Kanna M. (2017)
© 2016, Chiang Mai University. All rights reserved. In this work, a Ag/AgCl electrode was prepared from silver obtained from recovery of laboratory waste via the cementation technique. The extracted silver metal has purity of 89.4-97.0%, as examined by the Volhard’s titration. Silver was melted, poured into a cast, and elongated to be a silver wire with the size of 1 mm o.d. and length of 1.33 m. The wire was then used to prepare Ag/AgCl electrode by immerging it into a solution of FeCl 3 ⋅6H 2 O to form a AgCl film on the silver wire. This electrode was used as a working electrode for chloride determination or further fabricated as a reference electrode. For reference electrode preparation, the Ag/AgCl electrode was immersed in a saturated solution of KNO 3 contained in a glass tube plugging with agar at one end to act as a salt bridge. The working and reference electrodes were tested for potentiometric determination of chloride. Electrical potential was plotted versus logarithm of chloride concentration to obtain two linear calibration graphs, 5-20 ppm and 20-60 ppm, with the linear equation of y = 0.0018x - 0.0347 and y = 0.0006x - 0.0121, respectively. Moreover, the precision (%RSD) examined with 1 and 20 ppm of chloride solution was 0.9% and 2.7% (n=11), respectively. The prepared electrodes were used for determination of chloride in real samples comparing the results by t-test to those determined by the precipitation titration method. It was found that both methods have no significant difference at 95% confidence level.